A pH/ROS cascade-responsive and self-accelerating drug release nanosystem for the targeted treatment of multi-drug-resistant colon cancer. (1st January 2020) - Chang, Na; Zhao, Yufei; Ge, Ning; Qian, Liting
Abstract: The efficacy of chemotherapeutic agents for colon cancer treatment is limited by multidrug resistance (MDR) and insufficient intracellular release of the administered nanomedicine. To overcome these limitations, we constructed a pH/ROS cascade-responsive and self-accelerating drug release nanoparticle system (PLP-NPs) for the treatment of multidrug-resistant colon cancer. The PLP-NPs comprised a reactive oxygen species (ROS)-sensitive polymeric paclitaxel (PTX) prodrug (DEX-TK-PTX), a pH-sensitive poly(l -histidine) (PHis), and beta-lapachone (Lapa), a ROS-generating agent. We found that PLP-NPs could accumulate in tumor tissue through enhancement of the permeability and retention (EPR) effect, and were subsequently internalized by cancer cells via the endocytic pathway. Within the acidic endo-lysosomal environment, PHis protonation facilitated the escape of the PLP-NPs from the lysosome and release of Lapa. The released Lapa generated a large amount of ROS, consumed ATP, and downregulated P-glycoprotein (P-gp) production through the activity of NQO1, an enzyme that is specifically overexpressed in tumor cells. In addition, the generated ROS promoted the release of PTX from DEX-TK-PTX to kill cancer cells, while ATP depletion inhibited P-gp-mediated MDR. In vitro and in vivo experiments subsequently confirmed that PLP-NPs induced tumor-specific cytotoxicity and overcame the MDR of colon cancer. Our findings indicate that the use of the PLP-NPs system represents a promising strategy to counter MDR in the treatment of colon cancer.